E-Module Development Based on Problem Based Learning (PBL) on Material Class X High School Chemistry Association - Indra Wahyu Tampubolon (Jurnal Mekintek : Jurnal Mekanikal, Energi, Industri, Dan Teknologi, 2022)
This study aims to obtain: (1) PBL-based E-modules that have met the criteria for content eligibility, language eligibility, presentation eligibility, and graphic eligibility according to the National Education Standards Agency; (2) Students' responses to aspects of the appearance, material and benefits of PBL-based e-modules on chemical bonding materials. The type of research used is Research and Development (R&D) which has been modified as needed. This research was carried out in several stages, namely syllabus analysis according to the current curriculum, module analysis by researchers, module design and development, validation of e-modules by lecturers and teachers, and then evaluation of e-modules developed by students. The average result of validation by lecturers is 3, 53 which means it is valid and does not need to be revised and the average teacher validation is 3.86 which means it is valid and does not need to be revised. The average percentage of student satisfaction with PBL-based e-modules that have been developed is 77.87%. So it can be concluded that the E-module based on Problem Based Learning (PBL) in the chemical bonding material for class X SMA is valid and does not need to be revised. Based on the high student response, it means that students feel interested in the e-module.